Tegsedi (Inotersen): An antisense oligonucleotide approved for the treatment of adult patients with hereditary transthyretin amyloidosis - Gales, L (2019)
Tegsedi (Inotersen) is a chemicallymodified antisense oligonucleotide that inhibits the hepatic production of transthyretin (TTR). Several single-point mutations in TTR destabilize its structure, leading to the aggregation and accumulation of amyloid deposits in the nervous system, heart, kidneys and eyes. In July 2018, Tegsedi was approved by the European Commission for use in adults with stage one and two polyneuropathies. Later on, in October 2018, the FDA and Health Canada also approved its use for the treatment of the polyneuropathy of hereditary transthyretin-mediated amyloidosis (hATTR) in adults in the U.S. and Canada. Tegsedi was developed by Ionis Pharmaceuticals, the company that holds the global marketing license, together with its subsidiary Akcea Therapeutics.